BRCA1 intronic Alu elements drive gene rearrangements and PARP inhibitor resistance - Wang, Yifan; Bernhardy, Andrea J.; Nacson, Joseph; Krais, John J.; Tan, Yin-Fei; Nicolas, Emmanuelle; Radke, Marc R.; Handorf, Elizabeth; Llop-Guevara, Alba; Balmaña, Judith; Swisher, Elizabeth M.; Serra, Violeta; et al. (Nature communications, 2019)
BRCA1 mutant carcinomas are sensitive to PARP inhibitor (PARPi) therapy; however, resistance arises. BRCA1 BRCT domain mutant proteins do not fold correctly and are subject to proteasomal degradation, resulting in PARPi sensitivity. In this study, we show that cell lines and patient-derived tumors, with highly disruptive BRCT domain mutations, have readily detectable BRCA1 protein expression, and are able to proliferate in the presence of PARPi. Peptide analyses reveal that chemo-resistant cancers contain residues encoded by BRCA1 intron 15. Mechanistically, cancers with BRCT domain mutations harbor BRCA1 gene breakpoints within or adjacent to Alu elements in intron 15; producing partial gene duplications, inversions and translocations, and terminating transcription prior to the mutation-containing BRCT domain. BRCA1 BRCT domain-deficient protein isoforms avoid mutation-induced proteasomal degradation, support homology-dependent DNA repair, and promote PARPi resistance. Taken together, Alu -mediated BRCA1 gene rearrangements are responsible for generating hypomorphic proteins, and may represent a biomarker of PARPi resistance. BRCA1 mutations located within the BRCT domain result in proteasomal degradation and sensitivity to PARP inhibitors (PARPi). Here, the authors report genetic rearrangements in the BRCA1 gene that generate a BRCT-less BRCA1 protein isoform, which avoids degradation and leads to PARPi resistance.